Criminal Law Policy Against Perpetrators of Hoarding of Basic Commodities from the Perspective of Indonesian Legislation and Islamic Law - Zelvian, Padri; Gani, Ruslan Abd; Hidayati, Rahmi; Halim, Abdul; Syukri, Ahmad (International Journal of Religion Education and Law, 2025)
This study examines the legal policy regarding criminal sanctions against perpetrators of staple food hoarding in Indonesia, viewed from the perspective of national legislation and Islamic law. Staple food hoarding—defined as the act of storing goods in unreasonable quantities to create artificial scarcity and profit from price surges—is a serious threat to public welfare and market stability. In the Indonesian legal context, hoarding is regulated under Law Number 7 of 2014 on Trade, the Criminal Code (KUHP), and supporting regulations, which impose criminal sanctions in the form of imprisonment and substantial fines. However, the enforcement of these sanctions faces practical challenges in terms of monitoring, proving intent, and preventing repeat violations. From the Islamic legal perspective, hoarding, known as ihtikār, is explicitly prohibited as it violates the principles of justice and public interest (maslahah). The Prophet Muhammad condemned hoarding, and Islamic jurisprudence empowers authorities to impose discretionary punishments (taʿzīr) to prevent social harm. The findings indicate a significant convergence between the objectives of national and Islamic law in protecting economic justice and consumer rights, though their normative foundations and enforcement mechanisms differ. This paper concludes that an integrative approach—combining formal criminal law enforcement with the ethical and moral values of Islam—can enhance the effectiveness of anti-hoarding policies. Recommendations include stronger market supervision, public education on ethical business conduct, collaboration with religious institutions, and consistent law enforcement.